Copy number variations in AMY2B gene and amylase activity in Balkan dog breeds. - Jasmin Katica; Teufik Goletić; Aida Kavazović; Maja Varatanović; Ćazim Crnkić (PLoS ONE)
This study aims to estimate the number of AMY2B gene copies and measure serum amylase activity in several Balkan dog breeds. Additionally, it explores the relationship between these genetic and biochemical parameters. Blood samples from 85 dogs representing eight breeds were collected, DNA was extracted, and AMY2B copy numbers were determined using droplet digital PCR. AMY2B gene copies ranged from 7.7 to 18.4, with a mean of 12.4 ± 2.2. Significant breed-related differences were observed (p = 0.025), with Istrian Wire-Haired Hounds showing the highest mean copy number (13.9 ± 1.5) and Posavatz Hounds the lowest (10.8 ± 1.5). Serum amylase activity ranged from 3.3 to 17.8 µkat/L, with a mean of 8.7 ± 2.6, and showed significant interbreed differences (p = 0.004), with Barak breed displaying the highest activity. Serum glucose levels varied widely, but no significant interbreed differences were detected (p = 0.340). No significant correlation was found between AMY2B copy numbers and serum amylase activity or glucose levels. The study concludes that Balkan dogs have AMY2B copy numbers similar to other European breeds, likely reflecting historical agricultural practices in the region, thereby facilitating better starch digestion. While significant variations exist among breeds, the lack of correlation between gene copy number and amylase activity suggests that other factors influence enzyme levels.